Size of training firms and cumulated long-run unemployment exposure : the role of firms, luck, and ability in young workers' careers - Müller, Steffen [Verfasser]; Neubäumer, Renate [Verfasser] (My University, 2016)
"This paper analyzes how life-cycle unemployment of former apprentices depends on the size of the training firm. We start from the hypotheses that the size of training firms reduces long-run cumulated unemployment exposure, e.g. via differences in training quality and in the availability of internal labor markets, and that the access to large training firms depends positively on young workers' ability and their luck to live in a region with many large and medium-sized training firms. We test these hypotheses empirically by using a large administrative data set for Germany and find corroborative evidence." (Autorenreferat, BIBB-Doku)

"Auszubildende, die das Glück haben, in einer Region zu wohnen, in der es viele große Betriebe gibt, haben auf Dauer bessere Chancen auf dem Arbeitsmarkt. Das legt die Studie des Leibniz-Instituts für Wirtschaftsforschung Halle (IWH) nahe, in der ein deutlicher Zusammenhang zwischen der Größe des Ausbildungsbetriebs und der langfristigen kumulierten Arbeitslosigkeit aufgezeigt werden konnte. Dieser lässt sich nicht allein damit erklären, dass große Betriebe besserqualifizierte Auszubildende einstellen. Anhand von Daten, die bis in die 1970er Jahre zurückreichen, untersucht die Studie erstmals, wie sich die Größe eines Betriebs auf die kumulierte langfristige Arbeitslosigkeit auswirkt." (Hrsg., BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; G 1.2.2.4 Arbeitslosigkeit; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; Betriebsgröße; Arbeitslosigkeit; Auszubildender; Arbeitsmarktchance